2011
DOI: 10.1021/nn203817t
|View full text |Cite
|
Sign up to set email alerts
|

Smart Hybrid Materials Equipped by Nanoreservoirs of Therapeutics

Abstract: Nanobiotechnology enables the emergence of entirely new classes of bioactive devices intended for targeted intracellular delivery for more efficacies and less toxicities. Among organic and inorganic approaches currently developed, controlled release from polymer matrices promises utmost clinical impact. Here, a unique nanotechnology strategy is used to entrap, protect, and stabilize therapeutic agents into polymer coatings acting as nanoreservoirs enrobing nanofibers of implantable membranes. Upon contact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 41 publications
4
89
0
Order By: Relevance
“…In a recent publication, it was revealed that rabbit MSCs becaome senescent when expanded in culture. 24 In an effort to overcome this limitation, rabbit cells were cultured in cell culture medium containing 2% rabbit serum. To ensure the MSCs retained their plasticity, tri-lineage differentiation assays 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Regarding inflammation, the PLCL scaffold was biocompatible with no evidence of inflammation or giant cells in or around the struts of the template after 4 weeks implantation, which agrees well with previous studies by Jung et al, 15,16 where PLCL was also shown not to evoke an adverse inflammatory response in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent publication, it was revealed that rabbit MSCs becaome senescent when expanded in culture. 24 In an effort to overcome this limitation, rabbit cells were cultured in cell culture medium containing 2% rabbit serum. To ensure the MSCs retained their plasticity, tri-lineage differentiation assays 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Regarding inflammation, the PLCL scaffold was biocompatible with no evidence of inflammation or giant cells in or around the struts of the template after 4 weeks implantation, which agrees well with previous studies by Jung et al, 15,16 where PLCL was also shown not to evoke an adverse inflammatory response in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, it was revealed that rabbit MSCs became senescent when expanded in culture. 24 In an effort to overcome this limitation, rabbit cells were cultured in cell culture medium containing 2% rabbit serum. To ensure the MSCs retained their plasticity, tri-lineage differentiation assays were performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent years, a plethora of advanced biomaterials mimicking extracellular matrix were designed based on the micro-and nano-scale environment of tissues, using nanotechnologies as graphene, nanogrooves and carbon nanotubes [1][2][3][4][5][6][7][8]. More recently, and with the development of the third generation materials, there has been increasing interest in developing nanoparticles and nanoreservoirs containing active molecules able to bio-activate scaffolds [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%